Optimizing Strategic Transformation with EFQM Model: A Contingency Theory Perspective - Çağlar Yiğit; Kadir Varoğlu A. (Business Systems Research, 2025)
The EFQM Model, launched by the European Foundation for Quality Management (EFQM), is widely adopted by transforming organizations. Conducting research with an academic perspective on these models is crucial to comprehend their potential fully. While Contingency Theory has not yet gained widespread recognition for this purpose, it can play a fundamental role in shaping organizations’ transformational domains.